Definition of a CFD Methodology to Evaluate the Cylinder Temperature Distribution in Two-Stroke Air Cooled Engines. (December 2015) - Brusiani, Federico; Falfari, Stefania; Forte, Claudio; Cazzoli, Giulio; Verziagi, Paolo; Ferrari, Marco; Catanese, Dario
Abstract: On the basis of the operating cooling fluid, internal combustion engine cooling systems can be classified in two macro areas: air-cooling system and liquid-cooling system. In four-stroke engines, liquid-cooling system is generally preferred to the air-cooling system because of its efficiency in the engine heat dissipation. However, thanks to its simplicity, today the engine air-cooling system is still widely used in the engine market, especially on two-stroke engine applications like small motorbike, light aircraft, and handheld products. To assure the necessary heat waste in air-cooled engines, the key point is the optimization of the air flow over the cylinder external surface. Air flow separation from cylinder external surface can result in high temperature gradients inside the cylinder volume causing destructive heat problem for the engine. It can be avoided only by a fine optimization of the cylinder fin design placed externally to the cylinder surface. To fulfil this need, the definition of specific methodology to evaluate the air-cooling effect on the engine is mandatory. In the present paper, the authors present a 3D-CFD simulation methodology designed to perform a detailed evaluation of two-stroke air-cooled engines. The methodology was applied on two different engines equipping handheld brush-cutter machines. The optimization of the air-cooling system of such a machine is a very challenging task because the machine design must be very compact forcing all the engine parts to remain quite close each other. The simulation results are compared to experimental evidences in order to verify the validity of the proposed approach.